Influence of 2013 rule modification on scores and penalties awarded on two world judo championships - Stankovic, N.; Bratic, M.; Milosevic, N.; Escobar Molina, R. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: From 2009 International Judo Federation made significant rule changes in order to promote "positive judo", more attractive to the audience and with more scores and less negativity (penalties) (Calmet. Pierantozzi, Sterkowicz. Challis, & Franchini. 2017). The most important change was forbidding the leg grabbing techniques, first partially (2009). then totally (2013). Another significant modification was to reduce the importance of penalties and to modify the rules of the kumikata fight (grip fight). The aim of the research was to establish whether these modifications fulfill the IJF-s intention by analyzing the share of decisive scores (ippon), scores and penalties on two World Championship held before and after most important rules modification. Methods: By using free performance analysis software Lince 1.2.1 (Gabin. Camerino, Anguera y Castaner. 2012), a total of 240 male fights from World Championship 2011 and 2014 was analyzed in order to establish the share of scores and penalties. The statistical analysis Chi-square (y2) test with the significance of P < 0.0S was conducted to test the differences between frequencies of the samples. Z test was used to determine the proportion of the parameters and their individual difference between two championships. Results: In 2011 there were 81 decisive points (ippon). 43 positive scores (yuko. wazari 1) and 175 penalties, while in 2014 there were 96 ippons, 74 positive scores, and 337 penalties. On the first sight, there is a notable improvement in the number of positive scores, but also in the number of penalties. Results of the /2 test showed significant differences between two samples (sig=0.023). After conducting the Z test, results have shown the opposite tothe first impression, the share of ippons was higher in 2011 (27,09%) compared to 2014 (18,93%) sig <0.001. In addition, share of penalties was significantly (sig 0.005) higher in 2014 (66.47%) compared to 2011 (58.53%). while there were no significant differences (sig 0.827) in the positive scores obtained (14.83% compared to 14.60%). These data imply that giving the higher importance to positive scores and reducing the importance of penalties resulted with a higher number of both positive and negative actions, but unfortunately share of penalties was significantly higher. These results are in line with results obtained by Emerson et al. (2013) and Challis et al. (2018). Conclusion: The aim of promoting the "positive judo~ was partially accomplished by increasing the total number of positive scores, at the same time this result was contaminated by a huge increase in penalties awarded.